Posterior Tibial Slope Is Not Correlated With Meniscal Tears in Anterior Cruciate Ligament Reconstruction - Anthony El Alam, M.D.; Tracy El Khoury, M.D.; Joe Ghanimeh, M.D.; Joeffroy Otayek, M.D., M.Sc.; Sahar Semaan, M.D.; Pascale Salameh, Pharm.D., M.P.H., Ph.D., H.D.R.; Alfred Khoury, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation)
Purpose: To evaluate the impact of the tibial slope on the severity and location of meniscal tears in patients presenting with anterior cruciate ligament (ACL) rupture. Methods: We conducted a single-center retrospective observational study. We analyzed charts and records of patients who underwent ACL tear surgery between 2018 and 2021, excluding those with multiligamentous knee injuries or osteoarthritis. Posterior tibial slope was measured from lateral radiographs, and data on meniscal tears characteristics were collected, including laterality, anatomical location, blood supply zone, tear type, and treatment modality. Results: We included 749 patients (127 female, 622 male) who underwent ACL reconstruction (hamstring tendons, n = 59; bone−patellar tendon−bone, n = 659; quadriceps tendon, n = 31). Concomitant meniscal tears occurred in 361 patients (medial meniscus, 50.7%; lateral meniscus, 31.9%; both menisci, 17.4%). No correlation was found between posterior tibial slope and meniscal injury overall (P = .8). However, a significant correlation was noted between tibial slope and lateral meniscal body tear (P = .023). Conclusions: Our findings suggest that an increased tibial slope, as measured on lateral radiographs, is not indicative of concomitant meniscal tears. However, in cases in which meniscal tears did occur in patients with a high posterior tibial slope, they predominantly affected the lateral meniscal body. Level of Evidence: Level IV, prognostic, case series.